God’s victory and salvation. A soteriological approach to the subject in apocalyptic literature - Łukasz Bergel (HTS Teologiese Studies/Theological Studies, 2019)
One of the main points of interests in the apocalyptic literature is the salvation of God’s people. The topic is shown from a variety of perspectives. One of them is exceptional and very prominent in the apocalyptic genre – this is God’s victory. The theme of victory is a complex one. It consists of not only terminology and imagery of war, fight, rivalry, but also judgement, competition and kingdom. All of these motifs are being intertwined in the apocalyptic victory of God. The problem of God’s victory can be seen as schematic, which is present in many texts from the apocalyptic genre. Altering variables inside this scheme results in a different outlook on the salvation. It is used to give the shape of the narrative in the text. From the variety of apocalyptic literature, an exceptional place is given to the Apocalypse of John. The theme of God’s victory there, although it uses the Jewish traditions, is rewritten and upgraded to a new unique form. The goal of this article is to investigate how the mentioned schematic realises through different examples of apocalyptic texts and how it is incorporated and redefined in the Book of Apocalypse. What is God’s victory? Who is being conquered? With what means? What does it all mean to the salvation of people? These are the questions, which the author will try to answer in the article.